Incorporação de montmorilonita organofílica em termoplásticos para produção de nanocompósito - Barbalho, Gustavo Henrique de Almeida (2012)
The incorporation of organoclay in nanometer particles in thermoplastic polymers allows the production of nanocomposites with improved physical and mechanical properties compared to pure polymer. This study aims to evaluate the use organophilic montmorillonite in the formulation of nanostructured composites of polyethylene and polypropylene matrix by melt intercalation method by fusion. For clays compatible with the polymer matrices, they must be transformed into organophilic. The clay was organophilizated with quaternary ammonium salt, bromide hexa-decyl-trimethyl ammonium (HDTMA-Br). The characterization of the untreated clay were made by laser particle size analysis. The characterization of organoclay were made by X-ray fluorescence (XRF), X-ray diffraction (XRD), thermogravimetry (TG and DTA). The characterization of nanocomposites was done by transmission electron microscopy (MET) and tensile mechanical properties. The attaining of the nanocomposites of polypropylene/clay andpolyethylene/clay concentrated mixturesof clay/polymer were prepared in a homogenizer, with the objective of favoring the mixture in the counter-rotating duble extruded. The attained concentrated mixtures were added to the polymeric matrix in quantities that are necessary to achieve the normal level of 1% e 2,5% of clay mass extruded and injected. The superficial area (BET) was 5,1m2g-1 and the density 2,4 g.cm-3. The distribution of sizes is large with particles among 1 and 100μm. The results of the characterizations of the clay organophilic, by analysis of X-ray flowering (FRX), shows the cation exchange between sodium ions and cations of the salt. The results of X-ray diffraction (DRX) show the increase in basal interplanar distance, due to penetration of the carbon chains of the salt. The results of the analysis of TG and DTA presented two mass losses, at a dehydration range between related to the water in the layers between the silicate sheets, added to humidity and gas absorbed in the surface of the material. Through the results of tensile strength, the concentration of clay dispersion and its interaction with the matrix, directly influence the tensile strength of the specimens. The MET images reveal the morphologies of the nanocomposites, showing partially exfoliated structures with a predominance of some clusters.